2165. Risk Factors for CPE Colonization in Household Contacts of CPE Colonized/Infected Patients. (26th November 2018) - Farooqi, Lubna; Faheem, Amna; Armstrong, Irene; Borgundvaag, Emily; Coleman, Brenda; Green, Karen; Jayasinghe, Kithsiri; Johnstone, Jennie; Katz, Kevin; Kohler, Philipp; Li, Angel; Melano, Roberto; et al.
Abstract: Background: Carbapenemase-producing Enterobacteriaceae (CPE) are a global threat. Risk of transmission of CPE in households remains poorly understood Methods: Population-based surveillance for CPE colonization/infection is conducted in Toronto/Peel Region, Canada. In households with ≥1 consenting household contact (HC), groin, rectal swabs and urine samples are submitted every 3 months for both IC and HC until the IC has three consecutive negative swab sets. Swabs/urines are incubated overnight in BHI, direct PCR for carbapenemase genes is performed; specimens positive for PCR are then cultured. Results: Eighty-five households and 150 HC have been enrolled. Most common species/gene combinations in IC are: E. coli /NDM (33), E. coli /OXA48 (15), Klebsiella spp. /NDM (11). HCs have a median of eight swabs (range 2–14). 12 (8%) HCs were colonized with CPE (median 1.5 pos samples, range 1–8). IC and HC had same gene in 11(92%) cases, and same species/gene in seven (58%) cases. NDM+OXA48 ICs were more likely to have CPE colonized HC, see table. CPE colonized HC were older, more likely to be the IC's spouse (OR 32, 95% CI 4–260), and more likely to have travelled outside Canada (OR 9.7, 95% CI 1.2–78). Conclusion: HC colonization with CPE is uncommon, but not rare, and may be associated with either household transmission, or co-exposure of HC and IC via travel. Spouses are most often colonized. Disclosures: S. Poutanen, MERCK: Scientific Advisor, Speaker honorarium; COPAN: Speaker(but not part of a bureau), Travel reimbursement; Accelerate Diagnostics: Investigator, Research support; Bio-Rad: Investigator, Research support; bioMérieux: Investigator, Research support.